Efficiency of Hotel Management. Training of Specialists in Hotel Industry Field - USHAKOV, Roman Nikolaevich; KRYUKOVA, Elena Mikhajlovna; KHETAGUROVA, Valeriya Shotaevna; MUKHOMOROVA, Irina Viktorovna; ZELENOV, Vladimir Vladimirovich (Journal of Environmental Management and Tourism; Vol 11 No 2 (2020): JEMT Volume Xi Issue 2(42) Spring 2020, 2020)
The article deals with the main issues recently faced by the hospitality industry, as well as suggestions for their elimination and minimization. The study has shown that the main issues include the large gap between the practical and theoretical aspects of the training process, in addition to the insufficient amount of practice during the whole course of studying in the field of “Hotel industry”, which makes it impossible to adequately prepare graduates for competition on the labor market in the area of hotel service. Other issues include the lack of language teaching in higher education institutions that specialize in training hospitality business professionals, which undermines the entire education system aimed at communication with foreign guests. In the article, the authors analyze the problems of Russian higher education related to training professionals for the hospitality industry. These problems lead to the loss of competitiveness on the European and global market of educational services. The authors identify the key elements in the training of specialists that require improvements to engage in competition. After the study in this field was conducted, the ways of solving the identified problems were proposed. The solutions involved the principles of creating a competitive school of hotel management in Russia as a factor in the development of the resource potential of hotels. As a result, the prestige of studying in such higher education institutions rises.